(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
This paper proposes a new scheme of interpolation subdivision curve and surface using Bezier curve to achieve more realistic surface design. Different from the previous interpolation subdivision schemes, the normal vectors are used to generate a circle from a triangle which results in only three vertices and three edges. This improvement not only makes a curve smooth, but also produces sharp angles during subdivision. Examples of subdivision surface by this scheme are illustrated and compared to show the advantages of this scheme.